KORELASI TIPE BELAJAR DENGAN MINAT BELAJAR SISWA KELAS VIII PADA MATERI SISTEM PENCERNAAN DI SMP NEGERI 1 TOMA - Duha, Endang Putri S. (Universitas Nias Raya, 2024)
This study aims to investigate the relationship between learning styles and student interest in learning about the digestive system in Class VIII at SMP Negeri 1 Toma during the 2022/2023 academic year. This research is categorized as